Burnout as a Mediator of the Effect of Neuroticism Personality on Continuance Commitment among Nurses in Regional Public Hospitals in Jabodetabek - Tetty Winda Siregar; Siti Marliah Tambunan; Nilam Widyarini (Asosiasi Dosen Muda Indonesia, 2025)
Nurses working in Regional Public Hospitals (RSUD) face substantial workloads as they manage critically ill patients while coping with intense social and professional pressures. Such demanding conditions often lead to burnout-an emotional exhaustion state that can adversely affect individuals’ commitment to their organizations. One of the personal factors contributing to burnout is the neuroticism personality trait, which reflects a tendency to experience negative emotions such as anxiety, depression, and emotional instability. Individuals with high levels of neuroticism are more susceptible to burnout, which in turn may reduce continuance commitment due to heightened psychological strain and a stronger intention to leave the organization.This study aims to examine the effect of neuroticism on continuance commitment, with burnout serving as a mediating variable among nurses in Regional Public Hospitals across the Jabodetabek region. The research involved 200 respondents who met the criteria of being nurses employed in Regional Public Hospitals located within Jabodetabek, residing in the same region, and holding at least a Diploma III (D3) degree. Data were analyzed using SPSS version 23 and SmartPLS version 3.2.9.The results indicate that burnout significantly mediates the relationship between neuroticism and continuance commitment, with a coefficient value of 0.077, a t-value of 2.125, and a p-value of 0.034 (ρ < 0.05). These findings confirm that burnout functions as a mediating variable linking neuroticism to continuance commitment among nurses in Regional Public Hospitals within the Jabodetabek region.